Genome-Wide Identification and Expression Analysis of the Thioredoxin (Trx) Gene Family Reveals Its Role in Leaf Rust Resistance in Wheat (Triticum aestivum L.) - Bhurta, Ramesh; Hurali, Deepak T.; Tyagi, Sandhya; Sathee, Lekshmy; Adavi B, Sandeep; Singh, Dalveer; Mallick, Niharika; Chinnusamy, Viswanathan; Vinod,; Jha, Shailendra K. (Frontiers in Genetics, 2022)
Bread wheat (Triticum aestivum L. ; Ta) is the staple cereal crop for the majority of the world population. Leaf rust disease caused by the obligate fungal pathogen, Puccinia triticina L., is a significant biotrophic pathogen causing significant economic yield damage. The alteration in the redox homeostasis of the cell caused by various kinds of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in response to pathogenic infections is controlled by redox regulators. Thioredoxin (Trx) is one of the redox regulators with low molecular weight and is thermostable. Through a genome-wide approach, forty-two (42) wheat Trx genes (TaTrx) were identified across the wheat chromosome groups A, B, and D genomes containing 12, 16, and 14 Trx genes, respectively. Based on in-silico expression analysis, 15 TaTrx genes were selected and utilized for further experiment. These 15 genes were clustered into six groups by phylogenetic analysis. MicroRNA (miRNA) target analysis revealed eight different miRNAs targeted TaTrx genes. Protein-protein interaction (PPI) analysis showed TaTrx proteins interact with thioredoxin reductase, peroxiredoxin, and uncharacterized proteins. Expression profiles resulting from quantitative real-time PCR (qRT-PCR) revealed four TaTrx genes (TaTrx11-5A, TaTrx13-5B, TaTrx14-5D, and TaTrx15-3B) were significantly induced in response to leaf rust infection. Localization of ROS and its content estimation and an assay of antioxidant enzymes and expression analysis suggested that Trx have been involved in ROS homeostasis at span 24HAI-72HAI during the leaf rust resistance.